Penerapan Perencanaan Pajak Atas Pajak Penghasilan Pada Perusahaan Jasa Pt. X - Cahyaningtyas, Andinar Nastiti; Ismiyanti, Fitri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Tax planning is one way that can be done by taxpayers (either individuals or entities) to reduce the tax that must be paid. PT. X is a company engaged in rental services of heavy equipment and tools that support mining. This study aims to determine whether the company has carried out tax planning that is applied to corporate income tax and refers to applicable tax regulations. This research was conducted using qualitative research methods and conducting field research for data collection such as interviews, observation and analyzing the income statement. From this study the results that can be concluded are that the company has implemented tax planning for corporate income tax and has been implemented in accordance with applicable regulations.